2017
DOI: 10.1021/acsami.7b04659
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Morphological and Chemical Evolution of Nanoporous Stainless Steel by Liquid Metal Dealloying

Abstract: Nanoporous materials, especially those fabricated by liquid metal dealloying processes, possess great potential in a wide range of applications due to their high surface area, bicontinuous structure with both open pores for transport and solid phase for conductivity or support, and low material cost. Here, we used X-ray nanotomography and X-ray fluorescence microscopy to reveal the three-dimensional (3D) morphology and elemental distribution within materials. Focusing on nanoporous stainless steel, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Thereby, they concluded that one of the parameters is sufficient to characterize the structural size. As another material system, nanoporous stainless steel was analyzed by Zhao et al through liquid metal dealloying (LMD) using X-ray nano-tomography [77]. The authors report that the ISD plots are qualitatively similar to the ISDs of np-Au.…”
Section: Interfacial Surface Curvaturesmentioning
confidence: 99%
“…Thereby, they concluded that one of the parameters is sufficient to characterize the structural size. As another material system, nanoporous stainless steel was analyzed by Zhao et al through liquid metal dealloying (LMD) using X-ray nano-tomography [77]. The authors report that the ISD plots are qualitatively similar to the ISDs of np-Au.…”
Section: Interfacial Surface Curvaturesmentioning
confidence: 99%
“…This structure continues to corrode and forms a bicontinuous 3D network of pores by 33 min [Fig. 3(c)], analogous to the dealloying process which forms nanoand meso-porous structures for functional applications (Erlebacher et al, 2001;Zhao et al, 2017Zhao et al, , 2019Chen-Wiegart et al, 2013). The corrosion process slows in 33-185 min [Figs.…”
Section: D Nano-tomography Under a Liquid Molten Salt Extreme Enviromentioning
confidence: 99%
“…One solution to this is to dealloy parent alloys in a metallic melt, as studied in pioneering work by Harrison et al in the context of preferential leaching 26 . This liquid metal dealloying (LMD) has been more recently applied to form a range of porous structures including creating porous Ti out of Ti–Cu alloy 27 , 28 , porous Fe/Fe-alloys 29 31 using molten Mg, Ta, and Nb from their Ti-alloys using molten Cu 7 , 32 , and TiVNbMoTa nanoporous high entropy alloys 33 . With this method, the enthalpy of mixing is used to choose a system where the sacrificial metal (B) in a parent alloy (A–B) is miscible with the LMD agent (C), while the remaining metal is immiscible with the dealloying agent.…”
Section: Introductionmentioning
confidence: 99%